Prehospital administered fascia iliaca compartment block by emergency medical service nurses, a feasibility study - Dochez, Els (BioMed Central, 2014)
INTRODUCTION: Patients with a proximal femur fracture are often difficult to evacuate from the accident scene. Prehospital pain management for this vulnerable group of patients may be challenging. Multiple co-morbidities, polypharmacy and increased age may limit the choice of suitable analgesics. The fascia iliaca compartment (FIC) block may be an alternative to intravenous analgesics. However this peripheral nerve block is mainly applied by physicians. In the Netherlands, prehospital emergency care is mostly provided by EMS-nurses. Therefore we examined whether well-trained EMS-nurses are able to successfully perform a FIC block in order to ensure timely and appropriate effective analgesia. The study was study was registered in the Netherlands Trial Register (NTR-nr 3824). METHODS: Ten EMS nurses were educated in the performance of a FIC-block. Indications, technique, side-effects and complications were discussed. Hereafter the trained EMS-nurses staffed ambulance teams were dispatched to patients with a suspicion for a proximal femur fracture. After confirmation of the diagnosis, the block was performed and 0.3 ml/kg lidocaine (10 mg/ml) with adrenaline 5 μg/ml was injected. The quality of pain relief, occurrence of complications and patient satisfaction were evaluated. RESULTS: In 108 patients a block was performed. One hundred patients could be included. Every EMS nurse performed at least 10 FIC blocks. The block was effective in 96 patients. The initial median (NRS)-pain score decreased after block performance to a score of 6 (after 10 minutes), 4 (after 20 minutes) and 3 (after 30 minutes). At arrival at the Emergency Department the median pain score was 3. Dynamic NRS-pain scores when transferring the patient from the accident scene to the ambulance stretcher, during transportation to the hospital and when transferring the patient to a hospital bed were, 4, 3 and 3.5 respectively. Patient satisfaction was very high. No complications were noted. CONCLUSION: Additional educated EMS-nurses are able to successfully perform a FIC-block for providing acute pain relief to patients with a suspected proximal femur fracture.